2021
DOI: 10.1371/journal.pone.0251414
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a Sandwich-ELISA for simultaneous quantification of bovine pregnancy-associated glycoprotein in serum and milk

Abstract: Bovine pregnancy-associated glycoproteins (boPAG) are expressed by trophoblast cells in the bovine placenta. The multigene family of boPAG belongs to the group of aspartic proteases. The accumulation and circulation in maternal blood and milk has made boPAG very useful and important for pregnancy diagnosis in cattle. The goal of the present study was to develop and validate a new Sandwich-ELISA which allows the detection of boPAG in maternal serum and whole milk. Therefore, 984 serum and 928 milk samples were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Recently, Krebs et al [ 59 ], using ELISA newly developed in their lab, reported that the amount of PAG found in milk was 1.5% of the amount present in serum. The milk test identifies pregnancy at day 40 post-insemination, with a threshold value of 0.0165 ng/mL.…”
Section: Pag Trend During Gestation and Post-partummentioning
confidence: 99%
“…Recently, Krebs et al [ 59 ], using ELISA newly developed in their lab, reported that the amount of PAG found in milk was 1.5% of the amount present in serum. The milk test identifies pregnancy at day 40 post-insemination, with a threshold value of 0.0165 ng/mL.…”
Section: Pag Trend During Gestation and Post-partummentioning
confidence: 99%
“…BoPAGs were purified from cotyledons from different gestation stages by FPLC. A detailed description of the purification process can be found in Krebs et al (2021) [29]. A scheme of the different FPLC steps is shown in S1 Fig in S2 File.…”
Section: Resultsmentioning
confidence: 99%
“…A scheme of the different FPLC steps can be found in S1 Fig in S2 File. The resulting boPAG-containing fractions were stored at -20˚C until further analysis [29].…”
Section: Tissue Collection and Protein Purificationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is more sensitive when different class antibodies were used as the detection and capture antibodies with a broad spectrum of epitopes. Furthermore, the detection of multiple epitopes offers better sensitivity for detecting proteins that are present in low concentrations in a sample [11,12]. The DAS ELISA was established to determine the effective antigen yields in inactivated vaccines and thus represents an alternative for assessing the potency of FMD vaccines in vitro [13,14].…”
Section: Discussionmentioning
confidence: 99%